The Chairman’s leadership of corruption investigation management - LATIF, M.W; ADAM, S; SUYANTO, B (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Corruption crime has recently received more attention from the police. The management of investigating corruption cases is an interesting problem and it has had a big influence on both political and state life. The purpose of this study was to explain and identify the leadership of the team of investigators in the corruption cases investigating management. This research used a qualitative approach combined with a descriptive research method. The results of this study concluded that leadership is a process used by leaders to direct the organization and to provide examples of behavior for their subordinates in the investigation team.